Pengaruh Penggunaan Media Sponges Dakon Pada Materi FPB dan KPK Terhadap Hasil Belajar Siswa Kelas IV SD - Ayu Fitri (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This study aims to determine the learning outcomes of mathematics for highest common factor (hcf) and lowest common multiple (lcm) materials the by using ‘dakon’ sponges media in the SDN Kondangjaya III, East Karawang District, Karawang Regency. The method used is quasi-experimental, with non equivalent control group design research. The results shows that there is a significant effect between the learning outcomes of students who use media sponges and who did not use the media. The result showed sig = 0.000 0 α = 0.05, indicating that the hypothesis is accepted. It can be concluded that the results of student mathematics learning in get a positive influence by using ‘dakon’ sponges media.